Clinical significance of Staphylococcus aureus bacteriuria at a tertiary care hospital. (September 2013) - Al Mohajer, Mayar; Musher, Daniel M.; Minard, Charles G.; Darouiche, Rabih O.
Abstract Objectives: Staphylococcus aureus bacteriuria has been associated with invasive S. aureus disease. The current project describes the clinical significance of S. aureus bacteriuria. Methods: We conducted a retrospective chart review of patients who had S. aureus bacteriuria at the Michael E. DeBakey Veterans Affairs Medical Center, 2008–2010. Results: A total of 326 patients were included. Invasive S. aureus disease was documented within 12 months of bacteriuria in 56 patients (22.3% of methicillin-resistant S. aureus (MRSA) cases and 8.4% of methicillin-sensitive S. aureus (MSSA), p = 0.002). Multiple logistic regression indicated that MRSA bacteriuria (odds ratio (OR) 2.91, p = 0.010), absence of symptoms suggestive of a urinary tract infection (UTI) (OR 3.21, p = 0.019), inpatient status (OR 4.72, p = 0.003), and receipt of antibiotics active against S. aureus (OR 6.41, p < 0.001) were significantly associated with the presence of invasive S. aureus disease. Seventy-seven patients (23.6%) died within 12 months of the documented S. aureus bacteriuria. Age (OR 1.02, p = 0.025), absence of pyuria (OR 2.00, p = 0.029), the presence of invasive S. aureus disease (OR 2.05, p = 0.033), and inpatient status (OR 3.62, p < 0.001) were significantly associated with death. Conclusions: S. aureus bacteriuria is associated with significant morbidity and mortality. Patients without UTI symptoms, those with MRSA bacteriuria, and those without pyuria were more to likely to have worse outcomes (invasive S. aureus disease or death). Obtaining blood cultures should be considered in these cases.